2023
DOI: 10.3389/fgene.2023.1032346
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing in fetuses with short long bones detected by ultrasonography: A retrospective cohort study

Abstract: Background: Prenatal diagnosis of fetal short long bones (SLBs) was reported to be associated with skeletal dysplasias, chromosomal abnormalities, and genetic syndromes. This study aims to identify the genetic causes for fetal short long bones, and retrospectively evaluate the additional diagnostic yield of exome sequencing (ES) for short long bones following the use of conventional genetic testing.Methods: A cohort of ninety-four fetuses with sonographically identified short long bones was analyzed by trio-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Here, the overall mean GA at initial diagnosis was 22 weeks, with signs of fetal SF in ACH patients often first observed in the third trimester, aligning with previous research. 5,8 This study additionally revealed that TD can be detected earlier by ultrasound compared to OI. (B) Result of whole exome sequencing.…”
Section: Discussionmentioning
confidence: 64%
“…Here, the overall mean GA at initial diagnosis was 22 weeks, with signs of fetal SF in ACH patients often first observed in the third trimester, aligning with previous research. 5,8 This study additionally revealed that TD can be detected earlier by ultrasound compared to OI. (B) Result of whole exome sequencing.…”
Section: Discussionmentioning
confidence: 64%
“…A hypoplastic thorax should be distinguished from short‐rib thoracic dysplasia. As fetal exome sequencing has been applied for prenatal diagnosis, studies have shown that skeletal anomalies yield approximately 40% of diagnostic results, among which achondroplasia (28.9%) and osteogenesis imperfecta (18.4%) are the most common finding (Huang et al., 2023). In our study, the fetus exhibited shortening of the long bones and nasal bones and lateral temporal bone depression.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatally, the presence of shortened long bones may suggest conditions such as osteogenic imperfecta or achondroplasia, which are not specific to 3M syndrome. Eight cases of 3M syndrome in fetuses have been diagnosed, and additional features have been reported in seven cases (Chincoli et al., 2014; Guo et al., 2020; Hu et al., 2017; Huang et al., 2023; Huber et al., 2009; Meo et al., 2000; Smogavec et al., 2022): two fetuses exhibited increased nuchal translucency (NT; Guo et al., 2020; Huang et al., 2023); two fetuses had a hypoplastic thorax; one had short nasal bones (Meo et al., 2000; Smogavec et al., 2022); one fetus had head frontal bossing and bilateral temporal bone depression (Hu et al., 2017); and one had characteristic facial features, prominent heels, and slender long bones (Huber et al., 2009). The increased NT should be distinguished from RASopathies, and most RASopathies do not exhibit severely short long bones during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of drafting this study, another cohort study had been published from China, showing an additional diagnostic rate of 40.4% (38 out of 94 fetuses) with exome sequencing [ 26 ]. Similar to our study, it had shown that the diagnostic yield in fetuses with isolated short long bones was lower than in the fetuses with nonisolated short long bones but did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%